Factors Influencing the Purchase Decision of Ready-to-Cook Vegetable Packages - Anggrasari, Herdiana; Nada, Lintia Putri; Saputro, Wahyu Adhi (Jurnal Dinamika Sosial Ekonomi, 2025)
As urban lifestyles in Yogyakarta City become increasingly fast-paced, consumer preference has shifted toward practical, "ready-to-cook" solutions. This study analyzes the factors influencing the purchasing decisions of ready-to-cook vegetable packages, a market segment rapidly expanding due to high time-scarcity among city residents. Using a descriptive-analytical approach, data were collected from 38 respondents who had purchased ready-to-cook packages. Logistic regression analysis was employed to test variables including price (X1), product quality (X2), packaging (X3), practicality (X4), promotion (X5), and social recommendations (X6).The results indicate that while price, practicality, and social influence do not significantly impact purchasing decisions, packaging (X3) has a statistically significant influence. This suggests that for ready-to-cook products, packaging serves as a critical proxy for perceived freshness and hygiene, outweighing traditional drivers like price or promotion. However, the study’s small sample size (n=38) limits the generalizability of these findings, representing a preliminary insight into this niche market. This research contributes to the field by highlighting a shift in consumer behavior where "visual assurance" via packaging becomes the primary determinant in the convenience food sector, offering a new perspective for local agribusinesses compared to broader national studies.